An Overview Lavender Aromatherapy to Reduce The Intensity of Epigastric Pain in Gastritis Patients at Tthe Emergency Department - Wahyuni, Ni Wayan Sri; Sanjana, I Wayan Edi; Sukadana, I Gede (Babali Publisher, 2024)
Background: Gastritis is one of the health problems in the community with a high prevalence. One of the symptomatic signs of gastritis is epigastric pain, which can interfere with the patient's activities. Pain complaints are still felt in some patients despite pharmacological therapy. Purpose: To determine the effectiveness of lavender aromatherapy to reduce the intensity of epigastric pain in gastritis patients in the emergency room of Klungkung Hospital. Method: This case study investigates two patients with gastric pain who were treated in the emergency room using convenience sampling, a non-probability sampling technique. Findings: Ms. A before the intervention was given a pain scale of 4 out of 1-10, and after the intervention, she was given a pain scale of 2 out of 1-10. Ms. B before the intervention was given a pain scale of 5 out of 1-10, and after the intervention, she was given a pain scale of 3 out of 1-10. Conclusion: Lavender aromatherapy is effective in reducing epigastric pain in gastritis patients. It is hoped that lavender aromatherapy can be applied as one of the non-pharmacological therapies in an effort to reduce the intensity of epigastric pain in gastritis patients.